2023
DOI: 10.1371/journal.pone.0281393
|View full text |Cite
|
Sign up to set email alerts
|

Remote follow-up based on patient-reported outcomes in patients with chronic kidney disease: A qualitative study of patient perspectives

Abstract: Background Patient-reported outcomes (PROs) are increasingly used in outpatient follow-up. PRO-based remote follow-up offers a new healthcare delivery model, where PROs are used as the basis for outpatient follow-up in patients with chronic kidney disease. However, the patient’s perspective of this novel remote care delivery remains unknown. Objectives This study aimed to explore the patients’ experiences using PROs in remote care and how this mode of follow-up may enhance patient engagement. Design A qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
2
4
0
Order By: Relevance
“…In total, 12.9% of the patients needed course support, highlighting the benefit of having someone to call when problems occur. Prior findings from a parallel qualitative study, in which we interviewed 15 patients in the PROKID trial, support this finding [ 38 ].…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…In total, 12.9% of the patients needed course support, highlighting the benefit of having someone to call when problems occur. Prior findings from a parallel qualitative study, in which we interviewed 15 patients in the PROKID trial, support this finding [ 38 ].…”
Section: Discussionsupporting
confidence: 68%
“…However, data from this process evaluation study found that the physicians merely assessed 88.5% of the questionnaire responses received. This might indicate observer bias in the qualitative study [ 38 ], showing a falsely high result, although it might also indicate a false lower result in our study because of recall bias, as it seemed as if the physicians actually opened and assessed the patients’ PRO responses but forgot to approve and document the responses in the AmbuFlex database. However, it is a well-known challenge to get clinicians to assess and approve patients’ PRO responses [ 19 , 43 ].…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations